THE DEATH OF HAMAS LEADER ISMAI?L HENI?YYE IN THE TURKISH PRESS: AN ANALYSIS FROM THE PERSPECTIVE OF MEDIA AND IDEOLOGY - Erdogan, Mehmet; Alkan, Feryat (Yusuf ARSLAN, 2025)
This study, which deals with the function of the media as an ideological tool and the power of events to shape social perception, analyses how four different Turkish newspapers present the news of the assassination of Hamas leader Ismail Heniyye in terms of ideological and hegemonic discourse. In this context, it is analysed whether the news language, imagery and discursive structure in the news reports aim to direct the reader into a certain frame and create an ideological structure. The study shows that the newspapers Cumhuriyet, Sözcü, Sabah and Yeni Safak, which were included in the sample, each frame the incident according to their own political and ideological stance. While Cumhuriyet treated the incident as an international crisis, Sözcü newspaper criticised Israel's actions and portrayed the incident as part of the Palestinian-Israeli conflict. The newspapers Sabah and Yeni Safak, which take a conservative stance, treated Heniyye's death in the context of resistance and martyrdom and emphasised Turkey's role.

Medyanin ideolojik bir araç olarak nasil islev gördügü ve olaylarin toplumsal algiyi sekillendirme gücünün konu edindigi bu çalismada, dört farkli Türk ulusal gazetesinin, Hamas lideri Ismail Heniyye'nin suikast sonucu ölümüne iliskin haberleri ideolojik ve hegemonik söylem açisindan nasil sunduklari analiz edilmektedir. Bu baglamda incelenen gazete haberlerinde, haber dili, görseller ve söylemsel yapi, okuyucuyu belirli bir çerçevede yönlendirme ve ideolojik bir yapi olusturma amacinin tasinip tasinmadigi irdelenmektedir. Çalismada, örnekleme dahil edilen Cumhuriyet, Sözcü, Sabah ve Yeni Safak gazetelerinin her birinin kendi politik ve ideolojik duruslarina göre olayi çerçeveledigi ortaya çikarilmistir. Cumhuriyet gazetesi olayi uluslararasi bir kriz olarak ele alirken, Sözcü gazetesi Israil’in eylemlerini elestirerek olayi Filistin-Israil çatismasinin bir parçasi olarak sunmustur. Muhafazakâr bir bakis açisina sahip olan Sabah ve Yeni Safak gazeteleri ise Heniyye'nin ölümünü direnis ve sehadet çerçevesinde ele almis, Türkiye’nin rolü öne çikartilmistir.
TÜRK YAZILI BASININDA HAMAS LIDERI ISMAIL HENIYYE'NIN ÖLÜMÜ: MEDYA VE IDEOLOJI PERSPEKTIFINDEN BIR INCELEME
Keywords: Communication and Media Studies (Other); Iletisim ve Medya Çalismalari (Diger)